Indigenous Voices and Votes: Assessing the Dynamics of Indigenous Politics in Chile S Constitutional Referendum of 2022 - Disi-Pavlic, R (Cambridge University Press, 2024)
Many analysts have tried to discern the reasons behind the Chilean Constitutional Convention’s draft failure in the 2022 plebiscite. A significant explanation is the draft’s inclusion of indigenous rights and its plurinationality principle (Bargsted and González 2022). Despite Chile being unique in Latin America in its lack of constitutional recognition for its indigenous population (Acevedo 2021), most voters in indigenous areas appeared to have opposed the draft (Pairican 2022).1 What role did indigenous peoples and politics play in the rejection of the constitutional draft? The 2020–2022 constitution-making process was unique by Chilean standards in its inclusion of indigenous perspectives.2 The Constitutional Convention reserved seats for indigenous groups, elected their representatives through a special ballot, and had mechanisms for their consultation. The final draft proposed a plurinational state with indigenous representation and autonomy. Although some militant Mapuche groups abstained, many indigenous organizations viewed it as an avenue for greater political representation (Bidegain and Tricot 2021, 8–13). It addressed the limited electoral influence and absence of indigenous parties (Tricot and Bidegain 2020) and historic socioeconomic exclusions (Valenzuela, Toro, and Rojo 2017) that have caused some groups to adopt violent resistance (Alberti et al. 2023). This study identifies several claims about the role played by indigenous politics in the defeat of the constitutional draft and then contrasts them with district-level evidence. I describe indigenous leaders’ explanations for the “Approve” option’s defeat and use municipal data to examine voting patterns. Results reveal that most voters in indigenous districts opposed the draft but also suggest variation by ethnicity and stronger Approve sentiment in areas affected by violence and in rural, indigenous territories. © 2024 Cambridge University Press. All rights reserved.